Sex- and age-specific differences in the use of antiarrhythmic therapies among atrial fibrillation patients: a nationwide cohort study - Salmela, B; Jaakkola, J; Kalatsova, K; Inkovaara, J; Aro AL; Teppo, K; Penttilä, T; Halminen, O; Haukka, J; Putaala, J; Linna, M; Mustonen, P; et al. (Oxford University Press, 2025)
Aims: Atrial fibrillation (AF) patients frequently require active rhythm control therapy to maintain sinus rhythm and reduce symptom burden. Our study assessed whether antiarrhythmic therapies (AATs) are used disproportionately between men and women after new-onset AF.
Methods and results: The nationwide Finnish anticoagulation in AF registry-based linkage study covers all patients with new-onset AF in Finland during 2007-2018. Study outcomes included initiation of AATs in the form of antiarrhythmic drugs (AADs), cardioversion, or catheter ablation. The study population constituted of 229 565 patients (50% females). Women were older than men (76.6 ± 11.8 vs. 68.9 ± 13.4 years) and had higher prevalence of hypertension or hyperthyroidism, but lower prevalence of vascular disease, diabetes, renal disease, and cardiomyopathies than men. Overall, 17.6% of women and 25.1% of men were treated with any AAT. Women were treated with AADs more often than men in all age groups [adjusted subdistribution hazard ratio (aSHR) 1.223, 95% confidence interval (CI) 1.187-1.261]. Cardioversions were also performed less often on women than on men aged <65 years (aSHR 0.722, 95% CI 0.695-0.749), more often in patients ≥ 75 years (aSHR 1.166, 95% CI 1.108-1.227), while no difference between the sexes existed in patients aged 65-74 years. Ablations were performed less often in women aged <65 years (aSHR 0.908, 95% CI 0.826-0.998) and ≥75 years (aSHR 0.521, 95% CI 0.354-0.766), whereas there was no difference in patients aged 65-74 years.
Conclusion: Women used more AAD than men in all age groups but underwent fewer cardioversion and ablation procedures when aged <65 years.